PENYELENGGARAAN PENILAIAN HASIL BELAJAR SMK RUJUKAN PROGRAM KEAHLIAN TEKNIK KETENAGALISTRIKAN DI DAERAH ISTIMEWA YOGYAKARTA - EDY Supriyadi (Jurnal Edukasi Elektro, 2019)
This study aims to determine the implementation of the assessment of learning achievement on SMK Rujukan at Expertise Program of Electrical Engineering. The data sources of this study were school leaders (school principals, vice principals and heads of departments), teachers, and students on 5 SMK’s in Yogyakarta Province. Sample respondents were 8 (Principals/Vice Principals), 39 teachers, and 70 students. The results showed that in general the assessment of students learning achievement on SMK’s was fairly good. Based on the analysis of data from the teacher through the questionnaire, in the aspect of Planning Assessment obtained a mean value of 142.17 (72.66%), and a Standard Deviation of 16.23, fairly good. In the Instrument Development aspect, a mean value of 72.07 (75.07%) and a Standard Deviation of 6.23 was classified as fairly good. In the aspect of the Implementation of the Assessment, the mean value was 90.51 (68.56%), and the Standard Deviation was 10.89, which was fairly good. In the aspects of Usage and Reporting of Assessment Results, the average value is 70 (70%), and the Standard Deviation is 8.72, including fairly good. The assessment system of students’ learning achievement for SMK Rujukan in Yogyakarta still needs a lot of improvement